2005
DOI: 10.1128/aem.71.4.1836-1842.2005
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the Polyvalent Anti- Staphylococcus Bacteriophage K for Control of Antibiotic-Resistant Staphylococci from Hospitals

Abstract: The increasing prevalence of antibiotic-resistant staphylococci has prompted the need for antibacterial controls other than antibiotics. In this study, a lytic bacteriophage (phage K) was assessed in vitro for its ability to inhibit emerging drug-resistant Staphylococcus aureus strains from hospitals and other species of Staphylococcus isolated from bovine infections. In in vitro inhibitory assays, phage K lysed a range of clinically isolated methicillin-resistant S. aureus (MRSA) strains, S. aureus with heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(204 citation statements)
references
References 32 publications
7
196
1
Order By: Relevance
“…[49], vancomycin-resistant Enterococci [50][51][52], antibiotic-resistant Staphylococci [53,54], multidrugresistant Klebsiella pneumonia [55], imipenem-resistant [56,57] and multidrug-resistant Pseudomonas aeruginosa [58,59], antibiotic-resistant strains of Escherichia coli [60], and methicillin-resistant Staphylococcus aureus [61]. Today, there are several different antibacterial strategies derived from phages including enzybiotics (cloned host-specific, phageencoded lytic enzymes introduced to combat bacteria without the whole phage) and whole-phage therapy (introducing whole, viable phage to attack the infecting bacteria) [8,[62][63][64].…”
Section: Medical and Therapeutic Application Of Bacteriophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[49], vancomycin-resistant Enterococci [50][51][52], antibiotic-resistant Staphylococci [53,54], multidrugresistant Klebsiella pneumonia [55], imipenem-resistant [56,57] and multidrug-resistant Pseudomonas aeruginosa [58,59], antibiotic-resistant strains of Escherichia coli [60], and methicillin-resistant Staphylococcus aureus [61]. Today, there are several different antibacterial strategies derived from phages including enzybiotics (cloned host-specific, phageencoded lytic enzymes introduced to combat bacteria without the whole phage) and whole-phage therapy (introducing whole, viable phage to attack the infecting bacteria) [8,[62][63][64].…”
Section: Medical and Therapeutic Application Of Bacteriophagesmentioning
confidence: 99%
“…This approach with whole phages is largely based on the phage preparations used throughout the Former Soviet Union (FSU). Available data suggest that the use of phages as antibacterial agents is rather simple and has many advantages over antibiotics [8,19,53,54,65]. These advantages may be summarised as follows: (1) phages are specific and, therefore, cannot eliminate ecologically important bacteria (e.g., gut microflora); (2) phages cease to function soon after all their specific target host bacterial cells are destroyed and, hence, will disperse harmlessly; (3) human patients who are allergic to antibiotics can be treated with phages with no side effects; (4) phages are safe to use because they have no effect on mammalian cells; (5) phages can be administered in various routes-for example, topically, intravenous, or orally; (6) phages reproduce exponentially; hence, a single dose can be sufficient to treat an infection; (7) when resistant bacterial strains arise in the host, the phage has capabilities to overcome this resistance by mutating in step with the evolving bacteria; (8) production of phages is simple and inexpensive; (9) phages are ubiquitous and, thus, regarded as safe.…”
Section: Medical and Therapeutic Application Of Bacteriophagesmentioning
confidence: 99%
“…[23][24][25][26] Our study utilized bacteriophage K titers in a bacteriophage lock in the lumen of colonized catheters with concentrations of greater than 10 8 PFU/ml. Further work is needed to delineate an ideal dwell time, concentration, and systemic response to therapy, and the effectiveness of this approach in-vivo; it is virtually unknown how phage will interact when exposed to the intravenous environment in humans, and research is needed to understand what is likely to be a complex biological interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The modified phage generated by passing through less susceptible target strain can be used in combination with phageK to increase the host range. This study had also shown the potential of delivering the phage in the form of handwash or antistaphylococcal cream (O'Flaherty et al, 2005b). Merabishvili and colleagues (2009), demonstrated laboratory-based production and quality control of a cocktail, currently under evaluation, consisting of exclusively lytic bacteriophages for the treatment of Pseudomonas aeruginosa and S. aureus infections of burn wound.…”
Section: Aureus S Epidermidis S Saprophyticus S Chromogenes Smentioning
confidence: 99%